Estimating Return to Scale Production of Seaweed Farming in Tarakan City - Nurlela Machmuddin; Anisa Anisa; Rayhana Djafar; Sawitania Situmorang; Khaerunnisa Khaerunnisa (Jurnal Perikanan dan Kelautan, 2024)
The development of seaweed cultivation by farmers cannot be separated from production factors such as capital, seeds, labor, and land area, which greatly support the success of seaweed cultivation. This study aims to analyze the factors affecting seaweed production and how to return to scale. The research was conducted in Pantai Amal Village. The number of samples in the study was 59 seaweed farmers using the incidental sampling method. The data analysis technique used multiple linear regression analysis in the form of the Cobb-Douglas function logarithm using the SPSS 26 software. The results showed that simultaneously the capital factors (X1), seeds (X2), labor (X3), and land area (X4) jointly affect the production (sig=0.00). Only the farmer's capital partially showed a significant effect (0.00) smaller than the significance level of = 0.05. The business scale has shown increasing returns to scale with a coefficient value of 1.15, which means that all inputs used in production are increased by 1. The resulting production will be increased by 1, and the resulting production will increase by a more significant proportion, namely 1.15. Thus, seaweed farmers’ use of production factors is efficient.